The role of physical pretreatments on the hydraulic conductivity of natural sodium bentonites. Issue 3 (June 2015) - Puma, Sara; Dominijanni, Andrea; Manassero, Mario; Zaninetta, Luciano
Abstract The role played by physical pretreatments applied to sodium bentonites, such as pre-hydration, pre-consolidation and pore water salt removal, has been analyzed in this technical note looking at the results of a series of hydraulic conductivity tests that have been carried out using both deionized water (DW) and a calcium chloride solution (CCS) as permeants. Moreover, the effect of the presence of needling across the bentonite layer has also been investigated. The DW and CCS have been used in order to simulate respectively the short and long-term conditions performances of bentonite based barriers (e.g. geosynthetic clay liners) for pollutant control. Given an initial pre-hydration for all the tested samples, the experimental results have pointed out that physical pretreatments, such as pre-consolidation and salt removal, can significantly influence the response of bentonite to the cation exchange phenomenon and, in turn, to its swelling behaviuor and hydrated fabric or microstructure of the solid skeleton. When a geosynthetic clay liner (GCL) sample and two simple basic specimens, prepared in the laboratory with the same bentonite type, are preliminarily permeated with DW and, thereafter, with CCS in order to simulate long-term conditions in the field, the hydraulic conductivity (K) tests have shown that the presence of needling in GCL sample can strongly deteriorates its performances (i.e. from K = 2·10−11 m/s to K = 7·10−10 m/s) whereas, the other two basic bentonite specimens, without needling, present a much less degradation (i.e. from K = 2·10−11 m/s to K = 1.2–1.6·10−10 m/s), all the other test conditions being the same. On the other hand, laboratory test results also show that the pre-consolidation process is able to greatly improves the long-term behaviour of the basic bentonite specimens (K = 1.8·10−11 m/s referring to the CCS permeation) with negligible hydraulic conductivity variations referring to the short-term permeation phase with DW. Moreover, a specimen, further pre-treated by pore water salt removal with a cyclic squeezing process, showed in absolute the best hydraulic performances of the test series in both short and long-term conditions reaching a value of K = 8·10−12 m/s with DW and a K = 6·10−12 m/s in the long-term with CCS as permeant.